Optical fiber accelerometer for shock motion measurement - Nguyen, Van-Quyet; Chiang, Chia-Chin; Hsu, Hsiang-Cheng; Tsai, Liren (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
This study proposes an accelerometer to measure shock motion with a fiber Bragg grating (FBG) sensing element attached to a 3D-printed elastomer structure. The structure is designed to be able to measure shock motion from two directions (+X and –X) in 1D space using two optical sensors, FBG1 and FBG2, respectively. The deformation in the elastic structure leads to a change in the wavelength of the sensing element, and it is observed that the total Bragg wavelength shifts over the recorded acceleration range are 2.42 nm (FBG1) and 1.40 nm (FBG2) with a randomly generated acceleration between zero g and 600g (1g = 9.81 m/s2). Numerical simulations are also used to observe the suitable working frequency range for the proposed accelerometer and the suggested working frequency range for this sensor in the range of 40–240 Hz. Such sensors are typically used in impact testing, safety validation, and heavy industrial applications, where the magnitude of acceleration is extremely high but the frequency content remains relatively low.
Optica Applicata, Vol. 55, 2025, nr 2, s. 197-206
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka